Effect of Carbon Particles on the Permittivity and Acoustic Performance of Epoxy Compounds - Long, Dan; Wang, Li-Kun; Qin, Lei; Zhong, Chao; Zhang, Bin; Liu, Jing-Jing (Asian Journal of Chemistry, 2014)
The two-phase composite materials are fabricated by taking advantage of blending method, with the selecting substrate of epoxy 618 and carbon particles as the additive. Epoxy 618, curing agent and flexibility are mixed with the proportion of 10:1:1. The dibutyl phthalate is used as flexibility, ethylenediamine is selected as curing agent and the carbon particle is used as additives to improve the performance of epoxy compounds. Samples with a variety of mass ratios have been made. The dielectric properties and acoustic properties of the composites are measured. The results show that the dielectric constant, acoustic velocity and impedance of the composite material increases with the mass ratio of carbon.